The politics of prisoner abuse : the United States and enemy prisoners after 9/11 - Forsythe, David P. , 1941- (Cambridge University Press, 2011)
"This is a book about U.S. policies toward enemy prisoners after the Al Qaeda terrorist attacks on New York and Washington of September 11, 2001. It analyzes the central moral, political, and legal factors in the U.S. policy making process that led the George W. Bush Administration to abuse prisoners on a widespread basis. It also covers the early years of the Barrack Obama Administration"